INTERAKSI TRADISI LOKAL DAN AL-QUR’AN: Studi Kasus Tradisi Tarkam di Kelurahan Neroktog, Kecamatan Pinang, Kota Tangerang - Yogi Sulaeman; Kholilurrahman; Nurbaiti (LP2M Universitas PTIQ Jakarta, 2024)
The Tarkam tradition in the Neroktog community is one form of religious practice that demonstrates how the Qur'an lives within the social life of the community. This tradition involves the recitation of the Qur'an alternately for seven days and seven nights as a form of respect and prayer for the deceased. This study aims to analyze the Tarkam tradition from the perspective of the living Qur'an and to identify the religious, social, and cultural values contained within it. The methodology used in this study is a qualitative approach with interviews and participatory observation of the Neroktog community. The results show that the Tarkam tradition is not just a ritual, but also a means to maintain social harmony, strengthen community solidarity, and deepen the understanding of Islamic teachings. Furthermore, the study finds that this tradition is grounded in Islamic teachings, as evidenced by various hadiths that encourage prayer for the deceased. Additionally, the differing views of scholars regarding communal Qur'an recitation are discussed, reflecting the dynamics of religious practice within the community. The Tarkam tradition contributes to maintaining Islamic values and implementing the teachings of the Qur'an in community life. Thus, this study shows how local traditions can be a means to revive the teachings of the Qur'an and strengthen the spiritual bond between the living and the deceased.